STUDENT THINKING PROCESS IN SOLVING MATHEMATICAL PROBLEMS BASED ON APOS - Patma Sopamena; Syafruddin Kaliky; Nurlaila Sehuwaky; Kasliyanto Kasliyanto; Fahruh Juhaevah (IAIN Ambon, 2021)
factorization of algebraic expressions based on APOS. A qualitative-exploratory design was employed in this study, where the participants were asked to solve mathematical problems and perform think-aloud protocols. Interview was conducted to extract more interesting data and clarify the participants’ answers and logical analysis. The research subject was a student of class VIII of SMPN 23 Ambon which two students with the initials S1 and S2. The results showed that the thought process of students in solving the problem of factorization of algebraic tribes based on the APOS framework can be classified into 2 categories. The first category is complete thinking structure that was indicated by providing the correct answer to the problem. This process began with interiorization as Action, followed by coordination, encapsulation, reversal, regulation or de-encapsulation as Process towards the object. The second category or scheme is incomplete thinking structure, marked by making errors during the problem-solving process and fixing the errors after reflection. The incomplete thinking structure occurred on interiorization as Action and coordination, reversal and de-encapsulation as Process towards the object. The study found only two categories (complete and incomplete thinking structures), so it is possible for future research to find other categories.